(untitled) (diségno, 2021)
Starting from the graphic expressions pertaining to the artistic avant-garde and their influence on the performing arts, the aim of the article is to investigate the relationship between geometry and bodies in motion in costume and set designs dedicated to dance. The proposed readings concern the analysis of some emblematic representations of the artistic avant-garde that shared a profound interest in costume and set-design with those choreographers, dancers and music composers who were contributing to establish a vision of theatre strongly rooted in the socio-political worries of the time. The graphic interpretation dwells in the first instance on the sketches and costumes with the aim of tracing those geometric and distributive connections that exist between the totality of the human figure and the parts that define its dynamics. Subsequently some analytical schemas are proposed on the photograms of two ballets performed for the first time by Serge Diaghilev’s company, La Chatte (1927) and Les Noces (1923). In this case the choreographic structure, the arrangement of gestures in space, the directions and the dynamic elements are analyzed in order to frame and distinguish relationships between things and movements by means of force lines, in a mosaic of weights and graphic balances, seeing in the drawing a possible dimension of choreographic explication.